A Study of Vocabulary Learning Strategy Used By the Seventh Grade Students’ of SMP N 34 Muaro Jambi Academic Year 2017/2018 - Juliyati, Suyadi, Nurul Fitri (JELT: Journal of English Language Teaching, 2018)
Abstract The purpose of this research is to find out the strategy used by the students at Seventh grade of SMPN 34 Muaro Jambi Academic Year 2017-2018 in learning vocabulary.This study isa qualitative research using descriptive. This study focused onthe strategy used by the students. The participants of this research are 4 students (2 male and 2 female students) of seventh grade in SMPN 34 Muaro Jambi in acaemic year 2017/2018. The instrument of this research is interview that consist of 11 questions. The result of this research showed that it can be concluded that the strategy used by the students to study vocabulary is asking for teacher’s help, learning new vocabulary in a group and keep saying the new vocabulary. Then, the suggestions are: 1) For students to keep using even to add the strategy to learn the new vocabulary so that it can improve their skill in English vocabulary especially, and 2) For English teacher, it is better if the teacher can increase and add some more strategy in teaching new vocabulary to the students. Keywords: Learning Strategy, Vocabulary